Land uses changed the dynamics and controls of carbon-water exchanges in alkali-saline Songnen Plain of Northeast China. (December 2021) - Dong, Gang; Zhao, Fangyuan; Chen, Jiquan; Qu, Luping; Jiang, Shicheng; Chen, Jingyan; Xin, Xiaoping; Shao, Changliang
Highlights: C/H2 O fluxes vary greatly with agro-pastoral land uses in salinized Songnen Plain. Fenced and clipped meadow have higher transpiration: evapotranspiration ratio. Grassland C uptake is limited by VPD, while paddy is driven by Ta. Abstract: Land reclamation and grassland management are important land utilization pattern for effective use and restoration of alkali-saline land in agriculture-pasture transition regions. These large-scale land cover/land use changes (LCLUC) could impose profound and divergent impacts on terrestrial carbon (C) and H2 O cycling, hence require precise assessment of ecosystem CO2 uptake and water use differences due to specific land use of the same climate/soil landscape. We initiated clustered eddy covariance flux-tower observations and C/H2 O fluxes analysis of 4 adjacent representative land cover and grassland managements types on alkali-saline Songnen Plain, including fenced meadow (as reference land use), clipped meadow, degraded alkali-saline land and paddy field in 2018–2019. Results showed that differences in land use influenced the magnitude and temporal variation of net ecosystem productivity (NEP) and evapotranspiration (ET). Compared to fenced meadow, paddy field increased growing season C uptake by 63.3% and ET by 35.4%, while degraded alkali-saline land and clipped meadow decreased C uptake by 43.0% and 30.6%, and ET by 32.1% and 3.2%. Degraded alkali-saline land barely sequestrate C in dry year, whereas paddy field is least sensitive to inter-annual precipitation variation. Growing season C uptake was advanced in clipped meadow due to increased surface temperature, while monthly ET peaked early at May in paddy field. Agricultural use and specific grassland management also caused large differences in ET partitioning. Fenced meadow had greater ET partitioned into transpiration (69%) than clipped meadow (58%), degraded alkali-saline land and paddy field (41% and 34%, respectively). Water use efficiency appeared greater in clipped meadow and degraded alkali-saline land than in fenced meadow, and responded differently to abiotic factors. Overall, large-scale LCLUC has exerted significant influence on terrestrial C/H2 O balances and physical responses in alkali-saline Songnen Plain.